2007
DOI: 10.1089/vim.2007.0068
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Nonhuman Primate Tethering System for Evaluation of Acute Phase SIVmac251 Infection in Rhesus Macaques (Macaca mulatta)

Abstract: Infection of rhesus macaques with simian immunodeficiency virus (SIV) is the preferred animal model for the development and testing of human immunodeficiency virus (HIV) vaccines, and animals protected from SIV challenge by live attenuated vaccines are an invaluable tool for determining immune correlates of protection. The acute phase of SIV infection, in which immune responses are most critical for slowing disease progression, occurs within the first 4 weeks of exposure. The small window of time available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Recent studies have reported that, in spite of robust virus specific CTL responses in vaccinated animals that show protection to SIV, they appear to generate low responses to the more prevalent immunodominant epitopes (Keckler et al, 2007). Our findings further highlight the importance of regulating systemic cytolytic responses and provide evidence that leukocyte immunoglobulin-like receptors may play an important role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that, in spite of robust virus specific CTL responses in vaccinated animals that show protection to SIV, they appear to generate low responses to the more prevalent immunodominant epitopes (Keckler et al, 2007). Our findings further highlight the importance of regulating systemic cytolytic responses and provide evidence that leukocyte immunoglobulin-like receptors may play an important role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Using the tether system to study the acute phase after viral challenge, we recently demonstrated that all the macaques inoculated with the live-attenuated SIV vaccine were protected from pathogenic SIV infection [32]. As Table 1 shows however, while three (16037, 16041, and 16044) of four animals controlled SIV infection very efficiently and remained SP or LTNP, one vaccinated animal (16040, Mamu A * 01 + ) progressed to simian AIDS (SAIDS) at 118 weeks postchallenge.…”
Section: Resultsmentioning
confidence: 99%
“…These eight animals were placed on a tether system during the first 4 weeks of infection in order to demonstrate the usefulness of this technology in the study of viral immunology during the acute phase of infection. Details of the placement of the tether system, which allowed for blood sampling without sedation, are provided elsewhere [32]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include anentropic specificity and repertoire depth of CD8 T cells, 12 localized innate immune responses, 13 inhibition of CD4 T-cell recruitment, 14 CD8 T-cell-related transcription factor profiles, 15,16 env-specific antibodydependent cell-mediated cytotoxicity, 17 antibodies, [18][19][20] the location, effector functions and phenotype of CD8 + T cells, [21][22][23][24][25][26][27] the interactions between types of challenge and viral load, 28 and the contribution of CD4 + T lymphocytes [29][30][31] ; we also reported an association between increases in cytotoxic T lymphocyte (CTLs) specific for conserved epitopes and vaccine-induced protection. 32 However, the relative contribution of each of these factors to the overall protective response remains unclear. Therefore, it is likely that multiple effector mechanisms are involved in vaccine-induced protection and innate, humoral and cell-mediated immunity may all be required for protection.…”
Section: Introductionmentioning
confidence: 99%